Tackling Chronic Inflammation with Withanolide Phytochemicals-A Withaferin A Perspective - Emilie Logie; Wim Vanden Berghe (MDPI AG, 2020)
Chronic inflammatory diseases are considered to be one of the biggest threats to human health. Most prescribed pharmaceutical drugs aiming to treat these diseases are characterized by side-effects and negatively affect therapy adherence. Finding alternative treatment strategies to tackle chronic inflammation has therefore been gaining interest over the last few decades. In this context, Withaferin A (WA), a natural bioactive compound isolated from Withania somnifera, has been identified as a promising anti-cancer and anti-inflammatory compound. Although the majority of studies focus on the molecular mechanisms of WA in cancer models, recent evidence demonstrates that WA also holds promise as a new phytotherapeutic agent against chronic inflammatory diseases. By targeting crucial inflammatory pathways, including nuclear factor kappa B (NF-κB) and nuclear factor erythroid 2 related factor 2 (Nrf2) signaling, WA suppresses the inflammatory disease state in several in vitro and preclinical in vivo models of diabetes, obesity, neurodegenerative disorders, cystic fibrosis and osteoarthritis. This review provides a concise overview of the molecular mechanisms by which WA orchestrates its anti-inflammatory effects to restore immune homeostasis.